2017
DOI: 10.1007/s00270-017-1692-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Ablation Boundary Sharpness After Percutaneous Radiofrequency, Cryo-, Microwave, and Irreversible Electroporation Ablation in Normal Swine Liver and Kidneys

Abstract: Purpose To compare ablation boundary sharpness after percutaneous radiofrequency (RFA), cryo (CA), microwave ablation (MWA) and irreversible electroporation (IRE) ablation in normal swine liver and kidney. Material and Methods Percutaneous CT-guided RFA (n=5), CA (n=5), MWA (n=5) and IRE (n=5) were performed in the liver and kidney of 4 Yorkshire pigs. Parameters were chosen to produce ablations 2–3cm in diameter with a single ablation probe. Contrast-enhanced CT imaging was performed 24 hours after ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Our results show that the ability of 100 W–5 min MWA to rapidly create relatively large coagulation zones seems to be the key to simultaneously achieving large coagulation and small periablational areas. This is in agreement with the study by Cornelis et al [ 40 ], who assessed the transition zone created after MWA, RFA, cryoablation and irreversible electroporation in in vivo porcine kidney and liver, and observed that 5 min MWA created narrower transition zones than other techniques. Their ‘transition zone’ is clearly related to the ‘periablational zone’ since both zones are comprised of both viable and necrotic cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our results show that the ability of 100 W–5 min MWA to rapidly create relatively large coagulation zones seems to be the key to simultaneously achieving large coagulation and small periablational areas. This is in agreement with the study by Cornelis et al [ 40 ], who assessed the transition zone created after MWA, RFA, cryoablation and irreversible electroporation in in vivo porcine kidney and liver, and observed that 5 min MWA created narrower transition zones than other techniques. Their ‘transition zone’ is clearly related to the ‘periablational zone’ since both zones are comprised of both viable and necrotic cells.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, microwave ablation (MVA) has been shown to be a promising prospect in the treatment of HCC for its favourable efficacy due to larger ablation zones and less influence by the heat-sink effect [36][37][38][39]. However, MVA might be accompanied by relatively high complication rates caused by increased energy application and tissue destruction, thus limiting its use for the tumours close to critical structures.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal-basis ablation technique could generate coagulation necrosis instantly after application as well as a peripheral transition zone around the ablation region due to the temperature gradient [18]. All these changes can be determined by gross observation.…”
Section: Discussionmentioning
confidence: 99%